Development of Advanced High Strength Steel (AHSS), Including for Automotive Parts, Stainless Steel and Structural Applications - Naik, Dr. J. Murali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Safety and fuel efficiency are of utmost importance in the automotive industry. Over the past three decades, there has been a significant focus on enhancing the structural characteristics of motor vehicles. Advanced high strength steels have played a vital role in achieving these desired characteristics. Various types of advanced high strength steels, such as IF steel, Bake hardening steel, HSLA steel, Micro alloyed steel, Dual Phase steel, Ferrite Bainite steel, Martensitic steel, Hot formed steel, TRIP steel, TWIP steel, as well as austenitic and ferrite grade stainless steels, have replaced many structural components due to their superior strength and ductility. In this context, the causes behind the development of these steels from conventional to third generation have been examined, along with the strengthening mechanisms employed in the development of advanced high strength structural steels. A review of the literature indicates significant progress has been made from a metallurgical standpoint in the last decade.